Abnormalities of tau-protein and beta-amyloid in brain ventricle cerebrospinal fluid - Taláb, Radomír; Vališ, Martin; Řehák, Svatopluk; Krejsek, Jan (Neuro-endocrinology letters, 2009)
OBJECTIVE: Determination of various biomarkers, such as beta-amyloid, tau-protein, phosphorylated tau-protein in CSF and their sensitivity and specificity in neurodegenerative brain processes, in particular Alzheimer Dementia (AD), has been recently investigated to monitor their abnormalities in the CSF at early stages of diseases before the clinical manifestation. DESIGN AND SETTING: In the pilot group of our patients (10 men / 5 women) who underwent a drainage neurosurgical procedure for diagnosis of hydrocephalus, CSF was obtained from the brain ventricles and the influence of a different compartment of the CSF on the level of biomarkers, tau-protein and beta-amyloid, was investigated. RESULTS: The mean tau-protein level for all 15 patients was 812.0 pg/ml, with median value 363.7 pg/ml; while mean beta-amyloid level for all 15 patients was 526.7 pg/ml, with median value 239.5 pg/ml, respectively. The abnormal tau-protein and beta-amyloid levels were found in the subgroup of patients in whom hydrocephalus was caused by a severe pathological process, such as brain tumor. The beta-amyloid values were significantly lower also in comparison with our previously published results in patients with AD in the CSF obtained by lumbar puncture in the spinal canal. CONCLUSIONS: CSF in the brain ventricles is theoretically more stable and the values in this CSF probably provide more reliable informations for clinical diagnostic procedure than those for the CSF obtained by lumbar puncture in the spinal canal.
Keywords: dospělí; hydrocefalus; Female; dítě; biologické markery; předškolní dítě; Amyloid beta-Peptides; tau Proteins; Biomarkers; Adult; mladý dospělý; ženské pohlaví; mozkové komory; Adolescent; lidé; amyloidní beta-protein; Pilot Projects; pilotní projekty; Aged, 80 and over; Hydrocephalus; Male; Aged; mladiství; Alzheimer Disease; Child, Preschool; Young Adult; Alzheimerova nemoc; Cerebral Ventricles; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; proteiny tau; Humans